2014
DOI: 10.1021/jf503489v
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Stability of Lipid Nanoparticle Systems by Sonication during the Cooling Step and Controlling the Liquid Oil Content

Abstract: Aggregation of unstable particles in water limits the application of lipid nanoparticle (LNP) systems to foods despite the capability to encapsulate lipophilic bioactive components. This study exploits a preparation process that can reduce the aggregation of LNPs. Sonication during the cooling step (postsonication) for 4, 5, or 6 min was applied to increase the covering effect of Tween 20 on the particle. Additionally, LNPs were prepared using fully hydrogenated canola oil (FHCO) blended with 0-30 wt % liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Similar to the melting results, the solidification temperature, solidification peak height and solidification enthalpy also decreased with an increase in the percentage of the liquid lipid content. This is due to the presence of GT in NLCs that reduces the formation of eicosane crystals with the increase in liquid lipid (GT) content (Ban et al, 2014;Teeranachaideekul et al, 2008). These results are similar to the results from some prior studies where similar trends in the melting and solidification curves of NLCs were observed (Anantachaisilp et al, 2010;Ban et al, 2014;Teeranachaideekul et al, 2008).…”
Section: Differential Scanning Calorimetry (Dsc) For Slns and Nlcssupporting
confidence: 88%
“…Similar to the melting results, the solidification temperature, solidification peak height and solidification enthalpy also decreased with an increase in the percentage of the liquid lipid content. This is due to the presence of GT in NLCs that reduces the formation of eicosane crystals with the increase in liquid lipid (GT) content (Ban et al, 2014;Teeranachaideekul et al, 2008). These results are similar to the results from some prior studies where similar trends in the melting and solidification curves of NLCs were observed (Anantachaisilp et al, 2010;Ban et al, 2014;Teeranachaideekul et al, 2008).…”
Section: Differential Scanning Calorimetry (Dsc) For Slns and Nlcssupporting
confidence: 88%
“…There was insignificant change (p ≤ 0.05) in particle size, total drug content and entrapment efficiency of THC-SLNs and THC-SLNs gel at 4 ᵒ C ± 3 ᵒ C, 25 ºC ± 2 ºC/60% RH ± 5% RH, 40 ºC ± 2 ºC/75% RH ± 5% RH as given in Tables 3A and B. Though increase in the particle size was observed, however it was below 200 nm, required for enhanced permeation across the stratum corneum 52 . Latter may be assigned to the fact that on cooling SLNs, lipids are not fully crystallized and carbon chains are freezed heterogeneously.…”
Section: Stability Studiesmentioning
confidence: 83%
“…While exothermic peaks of bulk lipid were observed at ~ 44 °C and ~ 35 °C in cooling-calorigrams, the peaks of LNPs appeared at ~ 18 °C, which were attributed to crystal imperfections due to the limited space in nanoscale lipid particles. The lowered crystallization temperature compared with bulk lipid indicates the absence of large particles and destabilized LNPs in the dispersion 28 . These results suggest that M-LNP had very good colloidal stability, thus preventing LNP coalescence, flocculation, and aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Myricetin-loaded LNPs were prepared using an oil-in-water emulsion technique with a high-speed blender and sonication probe as reported previously 28 , with slight modifications. First, the lipid (5 wt%) and aqueous (95 wt%) phases were heated to 85 °C and mixed using a high-speed blender (Ultra-Turrax T25D,Ika Werke GmbH & Co., Staufen, Germany) at 8,000 rpm for 1 min and then at 11,000 rpm for 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation